Classroom assessment concepts and applications - Russell, Michael K. 1967-; Airasian, Peter W.; Airasian, Peter W. (New York, NY McGraw-Hill, 2012)
"Assessment is a daily, ongoing, integral part of teaching and learning. Classroom Assessment: Concepts and Applications explores how assessment is a key component of all aspects of the instructional process, including organizing and creating a classroom culture, planning lessons, delivering instruction, and examining how students have grown as a result of instruction.
The text also introduces pre-service teachers to new tools and approaches to classroom assessment that result from the infusion of computer-based technologies in schools. This is the most teacher friendly assessment textbook available--one that will inform a teacher's assessment practices for years to come"--Provided by publisher.
Chapter 1. The breadth of classroom assessment -- Chapter 2. Learning about students: early assessment -- Chapter 3. Lesson planning and assessment objectives -- Chapter 4. Formative assessment -- Chapter 5. Summative assessments -- Chapter 6. Designing, administering, and scoring achievement tests -- Chapter 7. Universal design for assessment -- Chapter 8. Performance assessments -- Chapter 9. Grading -- Chapter 10. Commercial standardized achievement tests -- Chapter 11. Computer-based technology and classroom assessment -- Appendix A. Standards for teacher competence in educational assessment of students -- Appendix B. Taxonomy of educational objectives: major categories -- Appendix C. Sample individual education plan -- Appendix D. Statistical applications for classroom assessment -- Appendix E. Some resources for identifying special needs.
Revised edition of: Classroom assessment / Peter W. Airasian, Michael Russell. ©2008.
Includes bibliographical references and indexes.
Keywords: Educational tests and measurements -- United States; Academic achievement -- United States -- Testing; Education -- United States -- Evaluation